2017
DOI: 10.1038/srep43796
|View full text |Cite
|
Sign up to set email alerts
|

Glycyrrhiza uralensis water extract enhances dendritic cell maturation and antitumor efficacy of HPV dendritic cell-based vaccine

Abstract: Licorice has been used as herbal medicine and natural sweetener. Here, we prepared Glycyrrhiza uralensis water extract (GUWE) and investigated the effect of GUWE on the maturation and function of dendritic cells (DCs) and its adjuvant effect on DC-based vaccine. We observed that GUWE dose-dependently promoted DC maturation and cytokine secretion through TLR4 signaling pathway. The capacity of DC to stimulate allogenic splenocyte proliferation was also enhanced by GUWE treatment. Compared with control group, GU… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 37 publications
0
28
0
Order By: Relevance
“…Our previous study showed that GUPS-C enhances the maturation and function of DCs and the antitumor efficacy of DC-based vaccine [23]. The immuno-enhancing activities of three GUPS fractions with undetectable levels of endotoxin were further investigated using the in vitro-cultured DCs and a mouse model in the current study.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Our previous study showed that GUPS-C enhances the maturation and function of DCs and the antitumor efficacy of DC-based vaccine [23]. The immuno-enhancing activities of three GUPS fractions with undetectable levels of endotoxin were further investigated using the in vitro-cultured DCs and a mouse model in the current study.…”
Section: Discussionmentioning
confidence: 92%
“…uralensis roots were collected from Yili in Xinjiang Uygur autonomous region, China. Polysaccharides were isolated using a previously-described procedure with some modifications [23]. In brief, 100 g of G. uralensis minced roots were extracted by 500 mL of petroleum ether twice at 60 • C for 1 h; then, the residues were collected and extracted with 500 mL of 80% ethanol twice at 60 • C for 1 h. The residues was collected and dissolved in 800 mL of distilled water.…”
Section: Preparation Of G Uralensis Crude Polysaccharides (Gups-c)mentioning
confidence: 99%
See 1 more Smart Citation
“…Licoricidin protected 3T3 fibroblasts against H 2 O 2 ‐induced oxidative stress (Kim, Xuan, & Park, ). Glycyrrhizae Radix et Rhizoma water extract promoted dendritic cell maturation and cytokine secretion and enhanced antitumor efficacy of human papillomavirus dendritic cell‐based vaccine (Aipire et al, ). Licoricidin could inhibit SW480 human colon cancer cells by inducing cycle arrest, apoptosis, and autophagy (Ji et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…TC-1 tumor mouse model was used to detect the antitumor effect of HPV + PFPS + DCs. Based on our previous studies, 20,22,23 tumor volumes can reach 2000 mm 3 in tumor mice around 30 days after TC-1 cell injection. Therefore, the one-week interval immunization was chosen.…”
Section: Pfps Treated Dcs Pulsed With Hpv Peptides (Hpv + Pfps + Dcs)mentioning
confidence: 91%